Peptides Hydrolysate Derived from Collagen of Snakehead Murrel (Channa striata) Skin Demonstrate Anti-cholesterol and Anti-oxidant activities - Wenny Silvia L. Br. Sinaga; Wangsa T. Ismaya; Debbie S. Retroningrum; Raymond R. Tjandrawinata; Maggy T. Suhartono (Bogor Agricultural University, Indonesia, 2020)
Anti-cholesterol and anti-oxidant play a crucial role to combat cardiovascular disease (CVD), due to formation of arterial plagues from oxidation of cholesterol. In the past decades, bioactive peptides demonstrating anti-cholesterol and anti-oxidant activities have emerged as the alternative drugs. In this study, acid soluble collagen was extracted from the skin of snakehead murrel and employed to induce secretion of collagenase by Bacillus licheniformis F11.4. The collagenases secreted were in turn used to produce peptides hydrolysate and were grouped in two distinct collagenase fractions, designated as fraction D and F. Peptides hydrolysate produced by the fraction D was found to demonstrate HMG-CoA inhibitor activity comparable to pravastatin and limited anti-oxidant activity. Meanwhile, peptides hydrolysate generated using the fraction F demonstrated anti-oxidant activity comparable to BHT (2mM), vitamin C (2mM), and vitamin E (2mM), but limited HMG-CoA activity. Combination of the fraction D and F resulted in substantial HMG-CoA inhibition and anti-oxidant activities.